1982
DOI: 10.1071/ch9821785
|View full text |Cite
|
Sign up to set email alerts
|

Ion-ion-solvent interactions in solution. II. Solutions of LiClO4 in diethyl ether

Abstract: .Vibrational spectra and 35Cl, 13C, 7Li and 1H n.m.r. spectra of anhydrous solutions of LiClO4 in diethyl ether have been studied. There is no evidence for the formation of free ions down to 0.1 M concentration of salt. Two salt species having concentration-dependent distributions are identified, these being contact ion pairs and ion aggregates. The salt species are solvated with one mole of solvent per mole of salt. The preferred conformation of the diethyl ether solvate molecule is trms-gauche. For pure dlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…A similar observation follows for lithium salt solutions in dimethylsulfone [7]. The ion pair formation has been treated in terms of dynamics in nitrate and perchlorate solutions in water and non-aqueous solvents [8][9][10][11]. It has been found that, for the anions in SSIPs and CIPs, the dephasing process is more rapid as compared to the solvated anions.…”
Section: Introductionmentioning
confidence: 60%
“…A similar observation follows for lithium salt solutions in dimethylsulfone [7]. The ion pair formation has been treated in terms of dynamics in nitrate and perchlorate solutions in water and non-aqueous solvents [8][9][10][11]. It has been found that, for the anions in SSIPs and CIPs, the dephasing process is more rapid as compared to the solvated anions.…”
Section: Introductionmentioning
confidence: 60%
“…In DEC solutions, the NMR measurements reported in Figure 1 show clearly the broadening of the bands with the LiClO 4 concentration, indicating a similar behavior to that in THF. Nevertheless, for a given concentration, the width of the NMR bands is even broader in DEC than in THF solutions ( 31 and that in DEC (that has a lower dielectric constant than diethyl ether), the 35 Cl NMR spectra obtained for the 0.05 and 0.1 mol L -1 concentrations are identical (also in non-normalized NMR spectra, not shown here), it can then be assumed that for the four concentrations studied here (0.05; 0.1; 0.5 and 1 mol L -1 ), no isolated perchlorate anion is present, the considered species being mainly neutral species. The presence of different oligomers at different concentrations for a given LiClO 4 /DEC solution has then to be considered to understand the reduction reactions of solvated electron in pulse radiolysis measurements of these solutions.…”
Section: Mullen 25mentioning
confidence: 99%
“…-anion has been attributed by some authors [18][19][20] to ion association in the solution. James and Mayes 19,20 have identified ion-solvent interaction in the Raman spectra of perchlorate solutions.…”
Section: Clomentioning
confidence: 99%
“…James and Mayes 19,20 have identified ion-solvent interaction in the Raman spectra of perchlorate solutions. However, because the v 1 mode is not IR active for unperturbed 4 …”
Section: Clomentioning
confidence: 99%